FAM50A as a novel prognostic marker modulates the proliferation of colorectal cancer cells via CylinA2/CDK2 pathway - Longhai Li; Zhaoshuai Ji; Guangyun Li; Hao Gu; Yan Sun (PLoS ONE, 2025)
Objective Colorectal cancer (CRC) is the third most prevalent malignant tumor type and the second leading cause of cancer-related death. Sequence similarity family 50 member A (FAM50A) plays a vital role in numerous disease processes, including tumor progression. This study aimed to evaluate the prognostic significance of FAM50A in CRC and to explore its role in CRC cell proliferation. Methods TCGA and GTEX databases and immunohistochemical staining (IHC) was used to study the expression of FAM50A in CRC tissues. Patient survival data were used to assess the prognostic significance of FAM50A in CRC using Kaplan–Meier analysis and Cox regression analysis. The Cell Counting Kit-8 (CCK-8), 5-ethynyl-2′-deoxyuridine (EdU), and colony-formation assays were employed to assess the impact of FAM50A on tumor cell proliferation. Flow cytometry was used to detect the changes of cell cycle. The cell cycle and cycle-related proteins were measured via western blotting (WB) to explore the potential mechanisms involving in cancer progresses. Results The results of IHC revealed a notable upregulation of FAM50A expression levels in CRC tissue compared with adjacent normal tissue. Moreover, FAM50A expression was positively correlated with N and TNM stages in 145 patients with CRC. Cox regression analysis and construction of a nomogram revealed that high FAM50A expression was a prognostic indicator for poor overall survival in patients with CRC. Knockdown of FAM50A decreased cell proliferation ability, the proportion of EdU positive cells, and the number of CRC cell colonies, whereas overexpressing FAM50A promoted proliferative phenotypes. Knocking down FAM50A induced a significant increase in the number of cells in the S phase. Meanwhile, CyclinA2 and CDK2 were significantly reduced after FAM50A knocking down. Conclusion FAM50A may be a novel prognostic marker for CRC, and may participate in regulating tumor progression by targeting the CyclinA2/CDK2 signal pathway.